Differential transcriptomic alterations in nasal versus lung tissue of acrolein-exposed rats - Alewel, Devin I.; Jackson, Thomas W.; Rentschler, Katherine M.; Schladweiler, Mette C.; Astriab-Fisher, Anna; Gavett, Stephen H.; Evansky, Paul A.; Kodavanti, Urmila P. (Frontiers in Toxicology, 2023)
Introduction: Acrolein is a significant component of anthropogenic and wildfire emissions, as well as cigarette smoke. Although acrolein primarily deposits in the upper respiratory tract upon inhalation, patterns of site-specific injury in nasal versus pulmonary tissues are not well characterized. This assessment is critical in the design of in vitro and in vivo studies performed for assessing health risk of irritant air pollutants. Methods: In this study, male and female Wistar-Kyoto rats were exposed nose-only to air or acrolein. Rats in the acrolein exposure group were exposed to incremental concentrations of acrolein (0, 0.1, 0.316, 1 ppm) for the first 30 min, followed by a 3.5 h exposure at 3.16 ppm. In the first cohort of male and female rats, nasal and bronchoalveolar lavage fluids were analyzed for markers of inflammation, and in a second cohort of males, nasal airway and left lung tissues were used for mRNA sequencing. Results: Protein leakage in nasal airways of acrolein-exposed rats was similar in both sexes; however, inflammatory cells and cytokine increases were more pronounced in males when compared to females. No consistent changes were noted in bronchoalveolar lavage fluid of males or females except for increases in total cells and IL-6. Acrolein-exposed male rats had 452 differentially expressed genes (DEGs) in nasal tissue versus only 95 in the lung. Pathway analysis of DEGs in the nose indicated acute phase response signaling, Nrf2-mediated oxidative stress, unfolded protein response, and other inflammatory pathways, whereas in the lung, xenobiotic metabolism pathways were changed. Genes associated with glucocorticoid and GPCR signaling were also changed in the nose but not in the lung. Discussion: These data provide insights into inhaled acrolein-mediated sex-specific injury/inflammation in the nasal and pulmonary airways. The transcriptional response in the nose reflects acrolein-induced acute oxidative and cytokine signaling changes, which might have implications for upper airway inflammatory disease susceptibility.